Effect of Forest Landscape Restoration on Ecosystem Services in Ethiopia: Review for Future Insight - Hirpa, Giche Yadesa; Letema, Sammy C; Ming’ate, Felix L. M (CV. Literasi Indonesia, 2023)
Forests are crucial covering 31% of the Earth’s land surface. Deforestation has caused damage to these forest landscapes limiting their ability to provide ecosystem services like provisioning, supporting, regulating, and cultural services. In response to this degradation issue, the concept of forest landscape restoration was introduced in 2000. This review aims to provide comprehensive studies of existing literature on the effect of forest landscape restoration and restoration time on reversing ecosystem service in Ethiopia. The goal is to inform evidence-based decision-making and guide research in this field. The review analyzed 16 studies conducted from 2011 to 2023 that covered aspects of forest landscape restoration. The findings indicated that these restorations had an impact on ecosystem services such as improving soil properties, storing carbon stack, enhancing species diversity, richness, evenness, and regeneration status, and benefiting community livelihood. However, the review found that most of the studies were limited to specific regions, little information on the cultural service, and there were inconsistencies in some research findings. In general, this study provides significant evidence supporting the importance of restoration as a viable strategy to rehabilitate degraded forest landscapes. It also highlights the importance of long-term monitoring and considering ecological conditions for sustainable restoration efforts in regaining ecosystem services.